2001
DOI: 10.1046/j.1444-2906.2001.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of met-myoglobin reductase on the color stability of blue fin tuna during refrigerated storage

Abstract: To investigate the reducing ability of met‐myoglobin (metMb) reductase, browned tuna meat was immersed with/without metMb reductase (0.103 unit/mL) for 120 min at 4°C. The metMb reductase activity of browned tuna meat significantly increased, whereas no significant change was observed in the control sample for the first 10 min of immersion (P > 0.05). After comparing the changes in metMb reductase activity, metMb content, Hunter’s ‘a’ and color, it was observed that the reductase did recover the bright red col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Myoglobin is an important chromoprotein which gives the redness to muscle. Generally, the redness of dorsal and ventral ordinary muscles is an important indicator of the quality of bluefin tuna, and the meat colour of tuna muscle changes from red to brown during chilled storage (Chiou, Pong, Nieh, & Jiang, 2001). The change of meat colour after slaughter is due to the increase of met-myoglobin which is produced by autoxidation of myoglobin.…”
Section: Pigment Contentmentioning
confidence: 99%
“…Myoglobin is an important chromoprotein which gives the redness to muscle. Generally, the redness of dorsal and ventral ordinary muscles is an important indicator of the quality of bluefin tuna, and the meat colour of tuna muscle changes from red to brown during chilled storage (Chiou, Pong, Nieh, & Jiang, 2001). The change of meat colour after slaughter is due to the increase of met-myoglobin which is produced by autoxidation of myoglobin.…”
Section: Pigment Contentmentioning
confidence: 99%
“…The importance of metmyoglobin in tuna flesh discoloration has been demonstrated by Chiou et al (2001) in studies with the closely related northern bluefin tuna. Chiou et al (2001) showed that addition of the enzyme metmyoglobin reductase to the surface of browned tuna meat could increase the redness of the meat by reducing the amount of metmyoglobin.…”
Section: Shelf Lifementioning
confidence: 94%
“…Chiou et al (2001) showed that addition of the enzyme metmyoglobin reductase to the surface of browned tuna meat could increase the redness of the meat by reducing the amount of metmyoglobin. This approach, like that of the present study, increases the color shelf life of tuna meat.…”
Section: Shelf Lifementioning
confidence: 98%
“…in respect of the colour. While Livingston and Brown (1981) still question the physiological importance of such enzymatic activities, it has been established by the working group of Jiang (Pong et al, 2000;Chiou et al, 2001) that met-Mb reductase influences the accumulation of met-Mb in chilled-stored tuna meat as an essential factor. Furthermore, it was found that immersion in met-Mb reductase could extend the colour stability of tuna meat, and that the enzymatic reduction of metMb by its reductase occurred during refrigerated storage (Chiou et al, 2001).…”
Section: Importance Of Colour Of Flesh For Quality Evaluationmentioning
confidence: 99%